Capability of the DKI Jakarta Provincial Revenue Service in the Implementation of Tax Revenue Administration (Modernization and Policy Improvement in Local Government) - Dini Annisa Pratiwi; Milla S Setyowati (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research discusses the Capability of DKI Jakarta Bapenda in the implementation of Tax Revenue Administration Modernization and Policy Improvement in Local Governments (TRAMPIL), which is a program to modernize tax revenue administration and improve policies in Indonesian local governments. Tax Revenue Administration Modernization and Policy Improvement in Local Governments (TRAMPIL) or Modernization of Tax Revenue Administration and Policy Improvement in Local Governments is designed to support the strengthening of tax revenue administration in Indonesia both in the Central and Local Governments. In this study, researchers used the Core capabilities theory by Leonard and Barton with indicators of Knowledge and Skills, Technical Systems, Managerial Systems, and Values and Norms. Capability in an organization or agency does not only refer to human resources, but refers to institutions, policy implementation, financial or financial resources that are good enough in realizing the vision and mission that has been built, management systems and technology that are good enough to provide public services, and leaders who can protect employees in order to achieve previously set goals The research method used in this research is a qualitative approach. The results of this study explain that Bapenda faces challenges related to the adaptation of employees and the public who are heading for retirement, network constraints that affect public services